Paroxetine prevented the down-regulation of astrocytic L-Glu transporters in neuroinflammation - Koki Fujimori; Junpei Takaki; Yukari Shigemoto-Mogami; Yuko Sekino; Takeshi Suzuki; Kaoru Sato (Elsevier, 2015)
The extracellular L-glutamate (L-Glu) concentration is elevated in neuroinflammation, thereby causing excitotoxicity. One of the mechanisms is down-regulation of astrocyte L-Glu transporters. Some antidepressants have anti-inflammatory effects. We therefore investigated effects of various antidepressants on the down-regulation of astrocyte L-Glu transporters in the in vitro neuroinflammation model. Among these antidepressants, only paroxetine was effective. We previously demonstrated that the down-regulation of astrocyte L-Glu transporters was caused by L-Glu released from activated microglia. We here clarified that only paroxetine inhibited L-Glu release from microglia. This is the novel action of paroxetine, which may bring advantages on the therapy of neuroinflammation.